2009
DOI: 10.1107/s002188980903982x
|View full text |Cite
|
Sign up to set email alerts
|

MIPS: metal interactions in protein structures

Abstract: MIPS (metal interactions in protein structures) is a database of metals in the three‐dimensional macromolecular structures available in the Protein Data Bank. Bound metal ions in proteins have both catalytic and structural functions. The proposed database serves as an open resource for the analysis and visualization of all metals and their interactions with macromolecular (protein and nucleic acid) structures. MIPS can be searched via a user‐friendly interface, and the interactions between metals and protein m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…But, in spite of aluminium being implicated as a trigger for the onset of Alzheimer's disease , very limited NMR studies involving aluminium have been reported. In a bioinformatics analysis carried out by us involving the residues of the Aβ12 fragment in various metal‐bound protein structures in the protein data bank , we find that there are very few aluminium‐bound structures reported as shown in Table S1. Of the reported structures, none are NMR structures.…”
Section: Discussionmentioning
confidence: 99%
“…But, in spite of aluminium being implicated as a trigger for the onset of Alzheimer's disease , very limited NMR studies involving aluminium have been reported. In a bioinformatics analysis carried out by us involving the residues of the Aβ12 fragment in various metal‐bound protein structures in the protein data bank , we find that there are very few aluminium‐bound structures reported as shown in Table S1. Of the reported structures, none are NMR structures.…”
Section: Discussionmentioning
confidence: 99%
“…Programs that predict metal binding sites include FINDSITE-metal 35 , MetSite 36 , SVM-Prot 37 , SeqCHED 38 , and metalDetector 39 . Databases for querying metal binding sites include MESPEUS 16 , MIPS 40 , MDB 41 , MetalPDB 42 , Metal-MACiE 43 , MINAS (http://www.minas.uzh.ch/), and PROMISE 44 . The services PDBsum 45 and PDBeMotif 46 include additional annotations.…”
Section: Introductionmentioning
confidence: 99%
“…without any other protein residue being involved. We narrowed these hits to tri-Asp sites in proteins at three-fold symmetry axes and combined them with hits from other searches using MIPS 26 , MetalS3 27 , and Metalmine 28 resulting in 14 sites, including LarE (Fig. 3).…”
Section: Crystallographic Characterization Of Metal Binding To the Trmentioning
confidence: 99%